Protective effect of phenolic-rich extract of Anona muricata Linn leaf on renal oxidative stress and inflammation in streptozotocin-induced diabetes in diabetic rats - Benjamin Olusola Omiyale; Bidemi Emmanuel Ekundayo; Makhosazana Siduduzile Mathenjwa-Goqo; Basiru Olaitan Ajiboye; Babatunji Emmanuel Oyinloye (Scientific African)
Diabetic nephropathy is one of the most pronounced complications that develops as a result of diabetes and it is a highly ranked caused of end-stage renal dysfunction. Anona muricata has been traditionally considered to be beneficial in treatment of diabetic complications. The present study delineates the ameliorative effect of the phenolic rich extract of Anona muricata on the expression of oxidative stress, inflammatory and renal function markers in the kidney of streptozotocin (STZ) induced diabetes in male rats. Induction of diabetes was achieved with a single intraperitoneal administration of streptozotocin (55 mg/kg body weight). The rats were randomly distributed into 6 groups of normal control, diabetic control, phenolic rich extract of Anona muricata (EAM) treated at (25, 50 and 100 mg/kg) and metformin (Glucophage). All treatments were orally administered for 28 days. Activity of antioxidant enzymes, malondialdehyde, kidney function markers, electrolytes and proinflammatory cytokines were conducted on the kidney. Anona muricata ameliorated the significant reduction to superoxide dismutase, catalase, reduced glutathione and glutathione peroxidase in the diabetic rats. The increase in the levels of malondialdehyde, interleukin 6 (IL-6) and tumour necrosis factor-alpha (TNF-α) were all attenuated. Creatinine clearance was significantly improved and other kidney function markers were regulated and other important markers regulated. The result of this study provides evidence that A. muricata may be able to manage diabetic nephropathy, through the regulation of oxidative stress and inflammation, creatinine clearance and regulation of kidney function markers.